Factors associated with youth engagement and participation in voluntary activities in Malaysia - Abdullah Sahimi, Nur Aishah Hamizah; Suandi, Turiman; Hamzah, Siti Raba'ah; Ismail, Ismi Arif (IDOSI Publications, 2014)
This paper identifies factors associated with youth engagement and participation in volunteerism. This paper is based on reviews of past studies on youth involvement in volunteering activities. In the literature review, several keywords including volunteerism, volunteering, youth, engagement and participation were identified. The theory of Planned Behavior by Ajzen (1991) was used as the basis to explain youth engagement and participation in volunteerism. In the reviews, the authors found that the main factors influencing youth engagement and participation are divided into two categories, external and internal factors including motivation, lack of time, the organizers, activities or program and demographic. Future research could provide a more definitive theoretical statement of youth volunteering and develop an additional proposition which may be derived from a more refined theory. Practical recommendations were discussed to assist individuals and organizations towards increasing youth engagement and participation in volunteerism.